Production d'arômes de type lactone par des levures - Alchihab, M.; Destain, J.; Aguedo, M.; Thonart, P. (Biotechnologie, Agronomie, Société et Environnement, 2010)
Production of aroma lactones by yeasts. Lactones are widely distributed in foods and beverages as aroma compounds. Their extraction from natural products is very expensive. Most of them can also be obtained in a chemical way, which is not well perceived by consumers. As an alternative, biotechnology proposes to use whole cells or enzymes to produce lactones by biotransformation or bioconversion of fatty acids. Different studies and patents have been conducted on that matter. In most cases, yeasts are the biological agent used. The main concerned lactones are γ- and δ-decalactones, γ-octalactone and γ-dodecalactone. This article describes lactones and their production by yeasts; particular attention will be devoted to the γ-decalactone.